Assessing coastal vulnerability along the Penarik Beach Terengganu - Ramizah, binti Mohd Raza (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Most of the beaches are experiencing erosion due to climate change. One of the factors that can erode the beach is the wave during northeast (NE) monsoon. In Malaysia, the NE monsoon affects the beaches in the east of Peninsular Malaysia and the beaches in the west of Borneo. Those beaches might subject to great erosion, including Penarik Beach that is located in the east of Peninsular Malaysia when the NE monsoon attacks the coastal areas. Furthermore, very few studies on coastal vulnerability assessment had been done in Malaysia. Therefore, this study aims Penarik Beach in order to assess its vulnerability level towards the NE monsoon by using Coastal Integrity Vulnerability Assessment Tool (CIVAT). Beach profiling and shoreline tracing methods are applied throughout this research. Besides, this research is also completed by determining the awareness level of localities by using questionnaires. This study has found out that some parts of Penarik Beach are eroding and there are also parts that experience accretion. Overall, vulnerability level at Kg. Mangkuk is low and the vulnerability at both Kg. Baru Penarik and Kg. Rhu Sepuluh are high. The survey by using questionnaires has also found out that awareness level among the locals is low.